RELAÇÃO FUNCIONAL ENTRE TATOS E INTRAVERBAIS EM PESSOAS COM TRANSTORNO DO ESPECTRO DO AUTISMO - Joely da Silva Andrade (2021)
By functional independence it is understood that the acquisition of the topography of a verbal response in a verbal function (for example, touch) does not imply the occurrence of the same topography with another verbal function (for example, mand). Studies in this area gained prominence from the 1960s onwards, but most of them have focused on tact and command operants. The present study seeks to avoid the use of the operant command due to the limited control of the establishing operation and aims to investigate the relationship of functional independence between the tact and intraverbal verbal operant, since these operants are more easily manipulated. Participants were three children with suspected or closed diagnosis of Autistic Spectrum Disorder (ASD). The study was divided into pre-test, action training, operant training and post-test phases. The training and tact test were performed with the presentation of printed images (non-verbal Sd) and the intraverbal training and test were performed only with questions (verbal Sd, without the presence of images). In the first phase, all participants underwent tact and intraverbal tests. One of the participants underwent tact training and intraverbal testing, while two participants underwent intraverbal training and tact testing. The results of this study pointed to dependence and functional independence relationships between the studied verbal operants. At each change in the experiment's phase, there was a decrease in the participants' performance, despite having obtained different results individually. In addition, while participant 1's data collection was performed in 17 sessions, participant 2 and 3's data collection was performed in 8 sessions, which demonstrates that participant 1 needed more time to issue more responses, reach criteria and change from one phase to another. The results also showed that participant 1 gave 0% of correct responses in the intraverbal test, which demonstrates that there was no acquisition of responses with an intraverbal function after tact training, that is, these results are in line with independence functional among the verbal operants. Participant 2 emitted 88% of correct responses in the tact test (phase 4), which confirmed the acquisition of responses with tact function, after the intraverbal training, that is, these results are in line with the functional dependence between the verbal operants. Participant 3 emitted 100% of correct responses in the tact test, which confirmed the acquisition of responses with the tact function, after the intraverbal training. The present study provides contributions to the field of autism and to the production of empirical data that support the VB-MAPP as a possible predictor of dependence and functional independence in individuals with developmental delays. Furthermore, it contributes to broadening the understanding of the relationships between verbal operants, especially intraverbal and tact, of the variables involved in their acquisition and of how these relationships are expressed in verbal behavior. Keywords: verbal behavior, verbal operants, autism.